2018
DOI: 10.3390/d10020045
|View full text |Cite
|
Sign up to set email alerts
|

Does Thinning Homogenous and Dense Regrowth Benefit Bats? Radio-Tracking, Ultrasonic Detection and Trapping

Abstract: Abstract:Renewal ecology promotes the creation and enhancement of landscapes that support biodiversity and ecosystem services for humans. Silvicultural thinning of forest regrowth to reduce tree competition represents a form of active management that may also benefit biodiversity, especially where secondary regrowth dominates. However, ecological responses to thinning can be complex, particularly for insectivorous bats whose ecomorphology is often related to vegetation structure. Furthermore, thinning may affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…Detection covariates: temp = minimum daily temperature; rain = total daily rainfall. Occupancy covariates: rain_apr-sep = winter rainfall; ndvi_apr-sep = mean winter NDVI; Harvest_pre5 = extent of recent (<5 years) harvesting; Harvest_5_15 = extent of intermediate (5 Nyctophilus spp., activity immediately increased fourfold (Law et al 2018a). The response by V. vulturnus may be short-lived (see also Gonsalves et al 2018), as monitoring reported here found that this species was negatively associated off-track with the extent of intermediate time since harvesting (5-15 years), but positively associated with the extent of older (5-15 years) fires.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…Detection covariates: temp = minimum daily temperature; rain = total daily rainfall. Occupancy covariates: rain_apr-sep = winter rainfall; ndvi_apr-sep = mean winter NDVI; Harvest_pre5 = extent of recent (<5 years) harvesting; Harvest_5_15 = extent of intermediate (5 Nyctophilus spp., activity immediately increased fourfold (Law et al 2018a). The response by V. vulturnus may be short-lived (see also Gonsalves et al 2018), as monitoring reported here found that this species was negatively associated off-track with the extent of intermediate time since harvesting (5-15 years), but positively associated with the extent of older (5-15 years) fires.…”
Section: Discussionsupporting
confidence: 64%
“…Two of the species are relatively common (N. gouldi, N. geoffroyi), but the third is listed nationally under threatened species legislation as Vulnerable (N. corbeni). Rather than attempting to monitor these species with an expensive trapping programme, targeted research has aimed to better understand habitat use and resource requirements (Law et al 2016) and response to disturbances such as thinning (Law et al 2018a) and fire (authors, unpubl. data) as the primary means of informing management.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…; Law et al . ). By contrast, declining forest will have more transparent canopy, more bare dead branches and a greater incidence of gaps.…”
Section: Introductionmentioning
confidence: 97%